(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Social media has become an integral part of daily life for college students, offering platforms for social connection, information sharing, and entertainment. However, its impact on mental health and well-being has sparked increasing concern. While social media can enhance communication and provide a sense of belonging, its negative effects on mental health, particularly among college students, cannot be overlooked. This paper examines the challenges associated with social media use, focusing on the relationship between social media engagement and mental health issues such as anxiety, depression, social comparison, cyberbullying, and sleep disruption. Research indicates that the curated nature of social media platforms can exacerbate feelings of inadequacy and trigger a cycle of negative self-assessment, leading to heightened levels of anxiety and depression. Furthermore, the fear of missing out (FOMO) and the addictive design of social media can significantly disrupt sleep patterns, further exacerbating mental health issues. The rise of cyberbullying has also been linked to online platforms, with many college students experiencing harassment that leads to feelings of isolation and stress. While social media offers several benefits, it also poses a significant challenge to the psychological well-being of students, making it critical for both individuals and institutions to address its potential harms. This paper calls for increased awareness and digital literacy programs that encourage mindful social media use and promote healthier online environments. Future research should explore the long-term effects of social media use and investigate strategies for mitigating its negative impacts, ensuring that social media remains a positive tool for personal and academic development.